(untitled) (Research, Society and Development, 2021)
Introduction: tuberculosis (TB) is a serious infectious disease, which presents itself as a public health problem in the world, especially in underdeveloped countries. The TB/HIV co-infection, demonstrated as a challenge to public health services, due to the prominent rates of treatment abandonment and appears as one of the major causes of death and hospital care in Brazil, São Paulo was one of the main states with the high number of people afflicted with Tuberculosis and HIV. Objective: to address the epidemiological profile of patients diagnosed with tuberculosis who are HIV carriers, analyzing the variables of incidence, mortality and treatment dropout in the period from 2011 to 2020. Methodology: This is a descriptive study of a quantitative nature, where it was carried out a comparative epidemiological review, correlating the annual public data collected in the Notifiable Diseases Information System (SINAN). Results and discussion: The state of Amazonas is the federation unit with the highest incidence of TB in Brazil, with 68.4 new cases per 100,000 inhabitants. The mortality rate in Brazil has suffered a reduction, although still alarming, about 6,000 deaths are reported every year, with the highest incidence being states with the highest mortality rates in the states of Amazonas and Pará, followed by Rondônia, Roraima and Tocantins maintained their position. the numbers of cases due to treatment dropout were significant, mainly in AM, PA and RO. Conclusion: It was possible to observe the importance of epidemiological surveillance of tuberculosis in HIV carriers in the North Region. A relationship between lower levels of education and treatment dropout was observed.